Возвращение: роман / Даниэла Стил; [перевод с английского Е. Каца] - Стил Даниэла (Эксмо, 2000)
Экземпляры: аб. (2011) / Инвентарный номер: 53775 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: С 80 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44